2019
DOI: 10.1155/2019/6374582
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Multichannel Blocker in Attenuating Intramyocardial Artery Remodeling in Hypertensive Rats through Increased Nitric Oxide Bioavailability

Abstract: Dronedarone is recommended for the treatment of atrial fibrillation. However, we do not know its effect on vascular remodeling. This study was designed to assess whether dronedarone has the potential to improve the intramyocardial artery remodeling induced by chronic hypertension. Ten-month-old male spontaneously hypertensive rats (SHR) were randomly assigned to receive dronedarone (100 mg/kg) or vehicle. Age-matched male Wistar-Kyoto rats served as controls. After 14 days of treatment, we studied the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The positive effects on progression, regression, and AF/AFL burden suggest that dronedarone may reverse atrial and ventricular remodeling. This suggestion is supported by results from animal studies of structural heart disease in which dronedarone was found to decrease remodeling through increased bioavailability of nitric oxide 19 and to cause regression of myocardial remodeling. 20–22 Moreover, dronedarone has previously been shown in the HESTIA study to reduce AF burden in patients with pacemakers who had paroxysmal or persistent AF.…”
Section: Discussionmentioning
confidence: 69%
“…The positive effects on progression, regression, and AF/AFL burden suggest that dronedarone may reverse atrial and ventricular remodeling. This suggestion is supported by results from animal studies of structural heart disease in which dronedarone was found to decrease remodeling through increased bioavailability of nitric oxide 19 and to cause regression of myocardial remodeling. 20–22 Moreover, dronedarone has previously been shown in the HESTIA study to reduce AF burden in patients with pacemakers who had paroxysmal or persistent AF.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have shown that chronic treatment with antihypertensive drugs produces regression of coronary artery remodeling [ 5 , 6 , 7 , 8 , 9 ]. However, our group has demonstrated this beneficial effect with short-term treatment with antiarrhythmic drugs (esmolol and dronedarone) [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%